Hubungan Personal Hygiene Saat Menstruasi dengan Kejadian Keputihan pada Remaja Putri Kelas X di SMA Negeri 3 Ambon - Arindiah Puspo Windari; Siti Rochmaedah; Syahfitrah Umamity (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
The cleanliness of the feminine area (personal hygiene), especially during menstruation, is often ignored by teenagers. If you don't maintain proper genital hygiene, then in damp conditions, fungi and bacteria in the feminine area will thrive. Using underwear that uses thin material and does not absorb sweat can also make the feminine area damp and smelly, making it easier for fungi and bacteria to nest and using sanitary napkins for more than 2-3 hours can make it easier for fungi and bacteria to nest in the feminine area. Objective: Aims to analyze the relationship between personal hygiene during menstruation and the incidence of vaginal discharge in class X teenage girls at SMA Negeri 3 Ambon. Methods: This study used quantitative research using a cross-sectional design. The sample in the study was 150 people. Data analysis using the Chi-Squere test Results: research shows that the use of underwear has a p value = (0.720), the length of use of sanitary napkins has a p value of sanitary napkins = (0.000) and how to clean female organs has a p value = (0.523). Conclusion: there is only a significant relationship between the length of use of sanitary napkins and how to clean the female organs and the incidence of vaginal discharge in class X teenage girls at SMA Negeri 3 Ambon. Meanwhile, what is not significant is the use of underwear and how to clean the female organs with the incidence of vaginal discharge in class X teenage girls at SMA Negeri 3 Ambon.